Pengujian Kualitas Sistem Informasi Monitoring Status Gizi dan Pendataan balita (SIGIZI POLSUB) Menggunakan Metode McCall - Khoirunnisa, Nurfitria; Perdana, Chepy; Rahayu, Slamet; Purnawan, Nunu Nugraha (Institut Teknologi Garut, 2025)
This research measures the quality of information systems using the McCall method with a case study of the Information System for Monitoring Nutritional Status and Data Collection of Toddlers (sigizi polsub). After conducting a literature study, this research was continued by distributing McCall questionnaires to 30 respondents who live in Rawalele Village, where the respondents are users of sigizi polsub. After the questionnaire results are collected, validity and reliability testing is then carried out to obtain valid and reliable variables and indicators. Furthermore, the variables and indicators that have been tested are used to measure the value of information system quality (Fa). Measurement begins with the process of weighting variables and indicators. Measurement uses weighting for each product operation variable, namely correctness, reliability, efficiency, integrity, and usability. The quality measurement results show that the correctness factor is 88.15%, Reliability is 84.51%, Efficiency is 84.75%, Integrity is 89.79%, and Usability is 79.68%. Overall, sigizi polsub is in the value range of 81%-100% which can be concluded that the quality of sigizi polsub according to the assessment of respondents in rawalele village is very high quality.